A Study on the Outcome of Targeted Temperature Management Comparing Cardiac Arrest Patients Who Received Bystander Cardiopulmonary Resuscitation With Those Who Did Not, Using the Nationwide TIMECARD Multicenter Registry - Liou, Fang-Yu; Tsai, Min-Shan; Kuo, Li-Kuo; Hsu, Hsin-Hui; Lai, Chih-Hung; Lin, Kun-Chang; Huang, Wei-Chun (Frontiers in Medicine, 2022)
1 Background and Purpose Targeted temperature management (TTM) is associated with decreased mortality and improved neurological function after cardiac arrest. Additionally, studies have shown that bystander cardiopulmonary resuscitation (BCPR) doubled the survival of out-of-hospital cardiac arrest (OHCA) patients compared with NO-BCPR. However, the outcome benefits of BCPR in patients receiving TTM are not fully understood. Therefore, this study aimed to investigate the outcome differences between BCPR and NO-BCPR in patients with post-TTM cardiac arrest. 2 Methods The TIMECARD multicenter registry established a study cohort and database for patients receiving TTM between January 2013 and September 2019. A total of 580 patients were enrolled and divided into 376 and 204 patients in the BCPR and NO-BCPR groups, respectively. 3 Results Compared with the NO-BCPR group, the BCPR group had a better hospital discharge survival rate (42.25% vs 31.86%, P=0.0305). A better neurological outcome at hospital discharge was also found in BCPR group. BCPR group had a higher average GCS score (11.3 vs 8.31, P<0.0001) and a lower average CPC scale (2.14 vs 2.98, P<0.0001). After adjusted by multiple logistic regression, bystander CPR was a significant positive predictor for in-hospital survival (OR=0.66, 95% CI: 0.45-0.97, P=0.0363). 4 Conclusions This study demonstrated that BCPR had a positive survival and neurological impact on the return of spontaneous circulation patients post-TTM.